RNA-mediated pathogenic mechanisms in polyglutamine diseases and amyotrophic lateral sclerosis - Chan, Ho Yin Edwin (Frontiers in Cellular Neuroscience, 2014)
Gene transcription produces a wide variety of ribonucleic acid (RNA) species in eukaryotes. Individual types of RNA, such as messenger, structural and regulatory RNA, are known to play distinct roles in the cell. Recently, researchers have identified a large number of RNA-mediated toxicity pathways that play significant pathogenic roles in numerous human disorders. In this article, we describe various common RNA toxicity pathways, namely epigenetic gene silencing, nucleolar stress, nucleocytoplasmic transport, repeat-associated non-ATG translation, RNA foci formation and cellular protein sequestration. We emphasize RNA toxicity mechanisms that involve nucleotide repeat expansion, such as those related to polyglutamine disorders and frontotemporal lobar degeneration-amyotrophic lateral sclerosis.